The Placement of Talent Management: Study on Manajemen Talenta Polri (MTP) - Wendi Afrianto; Fibria Indriati (Budapest International Research and Critics University, 2022)
Research on the concept of talent management in the public sector is still rarely done compared to similar research in business organizations. The National Police as part of a public organization that has the National Police Talent Management (MTP) program have also never conducted research related to the application of the talent management, even though MTP has been running for 6 years and problems are still found in its implementation. The application of MTP can be interpreted as a management process system for the regeneration of Polri officers as talent officers through the identification stage of Polri's talents to be determined as talents, then talent grouping, coaching and talent development is carried out and then talent placement. This article will discuss the concept of talent management, especially in the aspect of identifying key positions in the MTP placement pattern, the placement of Polri talent officers in the MTP program as well as the obstacles that occur in the implementation of MTP, especially the talent pool 2018 generation the HR function of the National Police Headquarters and the talents of the 2018 Police Force. The results of the study found 15 talents who had not been assigned to key organizational positions out of 38 existing talents, this will affect the motivation of the talents, as a result there will be a decrease in individual performance and not in accordance with the development plan Police talent. Then, the obstacles in the implementation of the MTP: first, the whereabouts of the talents of the National Police are still not fully known by the direct superiors or indirect superiors in the regional unit. Second, mentoring in the context of supervising and fostering Polri talents has not been optimal. Third, the evaluation process carried out is only administrative in nature, not a comprehensive MTP evaluation has been carried out.